论《洛阳伽蓝记》与《幽明录》中的志怪小说 = Study on mythical stories of the record of Buddhist temples in Luoyang and You Ming Lu - 陈慧燕 Chin, Hui Yan (2014)
六朝时期的志怪小说给唐代的唐传奇提供了许多的养分，让唐传奇得以用另一种崭新的姿态，更坚定、稳固的立足于文学史中。本文将以《洛阳伽蓝记》及《幽明录》为研究对象，探讨当中的志怪小说如何与时代产生连接，并透过当中的内容来展现南北朝时期的思想以及社会面貌。本论文分为五个部分。首先，绪论综述了相关文献的研究基础，对选题的动机做简单的阐述。第一章说明志怪小说的发展史在六朝时期的转变与转变的原因。接着对《洛阳伽蓝记》及《幽明录》做个简单的概述。由于佛教在当时非常兴盛，因此本文的第二章将会结合艺术特征来分析两个文本里的志怪小说，并从故事情节中发掘潜在的佛教义理。此外，也会针对这两部作品中的佛教志怪小说作出简单的比较研究。第三章旨在分析两部志怪小说的故事内容，探讨小说如何再现南北朝社会的风貌以及作者运用了何种艺术表现手法，将当时候的社会面貌勾勒出来。这两部作品在南北朝时都有着很高的文学地位，本章也会探讨这两部作品的主题思想及艺术特征的差异。结语总结了本文研究发现，说明志怪小说亦能如正史或者是诗歌一般，将当时的思想内容及人文风情，以另一种更为生动活泼、趣味盎然的姿态再现出来。 The mythical stories in the six dynasties have enormous influence on the legendary tales in Tang dynasty and it is a milestone in the history of Chinese literature. The report uses The Record of Buddhist Temples in Luoyang and You Ming Lu to discuss about the relationship between the supernatural tales and its times, and also show the ideological and social states in the northern and southern dynasties.The report consists of five sections. The introduction section summarises the fundamental research of the literatures and the significance of topic chosen. The first chapter includes the changes in the development of the supernatural tales in the six dynasties and the causes for these changes. The summary of The Record of Buddhist Temples in Luoyang and You Ming Lu is also included in the first chapter.The second chapter is about the analysis of the contents of supernatural tales and the hidden Buddhist concepts. Besides that, comparison between the literatures is done in this chapter.The third chapter mainly discusses about how the supernatural tales display social features in southern and northern dynasties. The artistic expression techniques which are used by the authors to show the social features in their works are also discussed in the chapter. In addition, the comparison between the two literatures on the theme and the artistic features will also be discussed in this chapter.Lastly, the conclusion recapitulates the main points and it is found that the supernatural tales can show the ideology and customs of the dynasties as how the poems and official history do.